PID Controller Design for Mobile Robot Using Bat Algorithm with Mutation (BAM) - Dwi Pebranti; Luhur Bayuaji; Yogesvaran Arumgam; Indra Riyanto; Muhammad Syafrullah; Nurnajmin Qasrina Ann Ayop (IAES Indonesia Section, 2019)
By definition, a mobile robot is a type of robotthat has capability to move in a certain kind of environmentand generally used to accomplish certain tasks with somedegrees of freedom (DoF). Applications of mobile robots coverboth industrial and domestic area. It may help to reduce risk tohuman being and to the environment. Mobile robot is expectedto operate safely where it must stay away from hazards such asobstacles. Therefore, a controller needs to be designed to makethe system robust and adaptive. In this study, PID controller ischosen to control a mobile robot. PID is considered as simpleyet powerful controller for many kind of applications. Indesigning PID, user needs to set appropriate controller gain toachieve a desired performance of the control system, in termsof time response and its steady state error. Here, anoptimization algorithm called Bat Algorithm with Mutation(BAM) is proposed to optimize the value of PID controller gainfor mobile robot. This algorithm is compared with a wellknownoptimization algorithm, Particle Swarm Optimization(PSO). The result shows that BAM has better performancecompared to PSO in term of overshoot percentage and steadystate error. BAM gives 2.29% of overshoot and 2.94% ofsteady state error. Meanwhile, PSO gives 3.07% of overshootand 3.72% of steady state error.